Structural Reforms and Stabilization Policies in the Euro Area - Kari E.O. Alho (The Research Institute of the Finnish Economy (ETLA), 2015)
Specifying a structurally built NKM model for EMU, and identifying in it the determinants of the potential output and the short-run cyclical factors, we consider structural reforms and monetary and fiscal policies in the euro area. Especially, we analyse whether structural reforms are deflationary or boost the economy in the short run and create spillovers within the euro area under the zero lower bound (ZLB) of the interest rate. We find that a structural reform towards a more competitive economy by lowering the mark ups in the goods and labour market is beneficial both in the short and long run, and both under normal and the ZLB situation in the financial markets. Coordination of reforms within the euro area is also called for, because the spillovers from reforms are typically negative. The national governments searching for an optimal structural policy can delegate the stabilization efforts to the ECB in a long-run equilibrium, but in the short run this separation does not hold in general. We find that in a recession the reform policy is typically curtailed, while in a boom it initially exceeds the long-run equilibrium of reform activity. Proper fiscal policy can alleviate this problematic feature in structural reform policies.
Keywords: E63; E61; F42; 330; structural reform; EMU; coordination